The Upaya Pemberdayaan Potensi UMKM di Desa Batu Ampar Melalui Pengenalan dan Seminar Literasi Keuangan - Aryanti; Aziza Riski Amanda (Jurnal Pengabdian Masyarakat, 2024)
This research is a form of community service carried out together with the activities of Real Work Lecture students at Raden Fatah State Islamic University, Palembang, which aims to introduce the concept of financial literacy to micro and medium enterprises in Batu Ampar Village, Sirah Pulau Padang District, Ogan Komering Ilir Regency. This research was carried out on February 23, 2024 at the Batu Ampar Village Hall Office. Financial literacy is a basic need for every economic actor. In the era of globalization and modern economic complexity, the ability to understand, manage and make good financial decisions is crucial. So, understanding of financial literacy needs to be improved in building a financially intelligent society at every level. This research uses qualitative methods, namely observation and discussion with small and medium enterprises in Batu Ampar Village. The results of observations and discussions that have been carried out show that public understanding of financial literacy is still quite minimal. This is a problem that must be considered considering the importance of knowledge about good financial planning as an effort to maintain the financial welfare of individuals and society.